2013
DOI: 10.3171/2013.7.jns121973
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial biomechanics following cortical contusion in live rats

Abstract: Object. The goal of this study was to examine the mechanical properties of living rat intracranial contents and corresponding brain structural alterations following parietal cerebral cortex contusion.Methods. After being anesthetized, young adult rats were subjected to parietal craniotomy followed by cortical contusion using a calibrated weight-drop method. Magnetic resonance imaging was used to visualize the contusion. At the site of contusion, instrumented force-controlled indentation was performed 2 hours t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…The effective elastic modulus was 100 -600 Pa, depending on the location and indentation depth, and grey matter was stiffer than white mater. More recently, AFM indentation showed that injury softens the brain and spinal cord (Moeendarbary et al, 2017), in agreement with previous investigations (Alfasi et al, 2013;Shafieian et al, 2009). Elastic moduli of the intact cortex were 200-300 Pa. All AFM studies of the rodent brain to date have neglected viscoelastic effects.…”
Section: Atomic Force Microscopy Studies In Ratssupporting
confidence: 86%
“…The effective elastic modulus was 100 -600 Pa, depending on the location and indentation depth, and grey matter was stiffer than white mater. More recently, AFM indentation showed that injury softens the brain and spinal cord (Moeendarbary et al, 2017), in agreement with previous investigations (Alfasi et al, 2013;Shafieian et al, 2009). Elastic moduli of the intact cortex were 200-300 Pa. All AFM studies of the rodent brain to date have neglected viscoelastic effects.…”
Section: Atomic Force Microscopy Studies In Ratssupporting
confidence: 86%
“…The feasibility of using diffusion tensor imaging in in-vivo detection and tracking of these structural changes, both during the progression of hydrocephalus and after shunting surgery, has recently been documented (Eskandari et al, 2014;Hattingen et al, 2010). Also Alfasi et al (2013) studied these structural damages and their effect on the brain tissue's viscoelastic properties. They concluded that factors such as edema and tissue's necrosis weaken the brain's elastic and viscous properties at the early stages of hydrocephalus.…”
Section: Resultsmentioning
confidence: 98%
“…With MRE, several studies of preclinical models have indicated its potential usefulness in TBI. The mechanical properties of the brain (as measured by MRE) have been found to change following brain injury in living rat and mice ( Alfasi et al, 2013 ; Boulet et al, 2013 ). Furthermore, using a TBI mouse model, a longitudinal study of MRE demonstrated that the elastic modulus of the injured brain tissue was higher than that of the contralateral hemisphere 1 h after injury ( Feng et al, 2017 ).…”
Section: Advanced Magnetic Resonance Imaging Based Techniquesmentioning
confidence: 99%